1985
DOI: 10.7567/jjaps.24s2.817
|View full text |Cite
|
Sign up to set email alerts
|

Successive Phase Transitions and Their Soft Modes in Ferroelectric Sr2Nb2O7

Abstract: The soft optic modes responsible for the successive phase transitions of Sr2Nb2O7 have been observed by the Raman scattering measurement. The characteristics of the soft modes are discussed in connection with the macroscopic properties of the successive phase transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Interestingly, the relatively strong modes observed in SrNbO 3.50 around 110 and 170 cm mode was assigned to the soft mode of the ferroelectric phase transition at 1615 K, based on Raman scattering experiments. 16 It was also observed in recent optical measurements and related to NbO 6 octahedra tiltings. 17 In agreement with Ref.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, the relatively strong modes observed in SrNbO 3.50 around 110 and 170 cm mode was assigned to the soft mode of the ferroelectric phase transition at 1615 K, based on Raman scattering experiments. 16 It was also observed in recent optical measurements and related to NbO 6 octahedra tiltings. 17 In agreement with Ref.…”
Section: Discussionsupporting
confidence: 58%
“…In the scenario observed here, T i decreases and also the concentration of the IC phase lowers (as seen by slope variations in Fig. 2), what happens to the R soft mode [5] that exists only in the IC phase (responsible for the low temperature dielectric anomaly at wK177 8C) is not so clear. It is anticipated that due to substitution of larger atom (Ba) on A-site the tilting of the oxygen octahedra is suppressed that affects T i markedly.…”
Section: Resultsmentioning
confidence: 88%
“…This transition was observed in the elastic compliance coefficients, electromechanical coupling, permittivity, and birefringence. The lattice instability studies revealed the soft optic modes responsible for the first and second phase transitions, and for the normal-IC phase transition [5]. As for Ba doped (Sr 1K…”
Section: Introductionmentioning
confidence: 99%
“…Only n = 4 and n = 5 members of the series have been observed so far [22][23][24]. By Cooling from above the Curie temperature, [25] Sr 2 Nb 2 O 7 undergoes the ferroelectric phase transition from space group Cmcm to Cmc2 1 , which is commonly referred to as the normal orthorhombic phase. On further cooling to 215°C, the compound changes to an incommensurate (IC) phase with space group Cmc2 1 [26,27].…”
Section: Introductionmentioning
confidence: 95%